Correlation between the multifractal structure, crystalline and photoluminescence properties of engineered CZO thin films. (18th May 2017) - Solaymani, Shahram; Ghaderi, Atefeh; Dejam, Laya; Garczyk, Żaneta; Sapota, Wiktoria; Stach, Sebastian; Dalouji, Vali; Luna, Carlos; Elahi, Seyed Mohammad; Elahi, S. Hossein
Abstract: Un-doped and Cu-doped ZnO (CZO) thin films were prepared by radio-frequency (RF) sputtering. The effects of Cu doping and annealing treatments on the microstructure, fractal features and photoluminescence of these thin films were investigated by different characterization techniques including X-ray diffraction, X-ray photoelectron spectroscopy (XPS), atomic force microscope (AFM), photoluminescence (PL) and Rutherford back scattering. The results indicated that the Cu-doping enhanced the c-axis preferential growth of the ZnO films, however introduced crystal defects and micro tensions in the crystal lattice reducing the crystal size and the lattice parameter c. The XPS studies revealed that the states of Cu in the doped films were Cu 1+ and Cu 2+, and the PL characterizations showed that the incorporation of Cu in the crystalline structure of the ZnO thin films produced a green emission at 530 nm. The annealing treatments increased the crystal size in the [001] direction and reduced the lattice parameter c due to the accommodation of the Cu atoms in equilibrium positions. Also, these treatments increased the intensity of the PL peaks. All samples displayed a micromorphology that was successfully described as a fractal structure that can be decomposed into local motifs whose essential features varied with the Cu-doping and/or annealing temperature in agreement with their mentioned influence on the crystallization process of the samples. Highlights: We presented results of Cu doped ZnO thin film's surfaces at different annealing temperatures. We characterized the micromorphology of thin films synthesized by (RF) magnetron sputtering. We used atomic force microscopy and multifractal geometry. We determined the singularity spectrum f(α) of the multifractal structure.